ANIMATED DIDACTIC TESTS FOR LABORATORY SEMINARS IN PHYSICS - FILIPEK, Josef (Trends in education, 2010)
Conventional didactic test are mostly used for the examination of students or for checking their knowledge. Animated didactic tests can be applied by the examination as well; though, their main benefits consist in their cognitive function. In case the distracters are selected appropriately, the cognitive functions are even more emphasized. Students of several study specializations of full and part-time studies attend the laboratory seminars in physics at the Mendel University in Brno. Animated didactic tests help to clarify the theoretical base as well as the practical solution of individual tasks.
Keywords: Animated didactic tests; laboratory seminars; physics; interactivity.